2020
DOI: 10.1007/s00109-020-01874-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of intratumor heterogeneity: challenges and opportunities

Abstract: In this review, we highlight the role of intratumoral heterogeneity, focusing on the clinical and biological ramifications this phenomenon poses. Intratumoral heterogeneity arises through complex genetic, epigenetic, and protein modifications that drive phenotypic selection in response to environmental pressures. Functionally, heterogeneity provides tumors with significant adaptability. This ranges from mutual beneficial cooperation between cells, which nurture features such as growth and metastasis, to the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
191
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(201 citation statements)
references
References 201 publications
(242 reference statements)
3
191
2
5
Order By: Relevance
“…interpreted as a more homogeneous distribution across the tumor area in both groups (ANOVA: p = 0.0039). Increased intra-tumor heterogeneity has previously been identified as an important indicator for therapy resistance and poor overall survival (46)(47)(48). However, for L-phenylalanine, we did not observe a difference in heterogeneity (dynamic range) between both groups (Student's t-test: p = 0.9443; Fig.…”
Section: Resultscontrasting
confidence: 46%
“…interpreted as a more homogeneous distribution across the tumor area in both groups (ANOVA: p = 0.0039). Increased intra-tumor heterogeneity has previously been identified as an important indicator for therapy resistance and poor overall survival (46)(47)(48). However, for L-phenylalanine, we did not observe a difference in heterogeneity (dynamic range) between both groups (Student's t-test: p = 0.9443; Fig.…”
Section: Resultscontrasting
confidence: 46%
“…Intratumoral heterogeneity is one of the leading causes of therapeutic resistance and treatment failure, and one of the main reasons for poor overall survival in cancer patients. Importantly, it has been shown that targets against which therapeutics are available are not expressed in a homogeneous manner in tumor tissues [ 21 , 22 , 38 ]. Therefore, combination approaches that target cancer cells and tumor vasculature can potentiate the therapeutic response [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following up on the promising results we obtained in both in vitro and in vivo studies, we explored the possibility of combined targeting of endothelial and cancer cells in vitro, in order to improve the efficacy of targeted PDT. We hypothesized that dual targeting of receptors on endothelial and cancer cells is likely beneficial in tumors with high heterogeneity of target expression and/or intermediate/low target expression levels [ 21 , 22 ]. In line with this, our previous study showed that dual targeting of two cancer cell targets, namely HER2 and CAIX, improved tumor imaging in an orthotopic model of breast cancer [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…De hecho, esto podría generar en el futuro una novedosa terapia personalizada para la metástasis en la que se proporcionarían medicamentos específicos para desafiar la viabilidad de las células cancerosas que atienden a los órganos moleculares clave específicos de cada órgano. (Figura 3 y 4) d) Buscando factores de embudo o centrales de señalización , el Dr. Ramón y Cajal (12,13) presentó los datos clínicos de la expresión de factores de señalización en tumores humanos. La expresión fue bastante heterogénea en la mayoría de ellos (pAKT, pmtor, pMAPK, pS6) pero 4EB-P1 y especialmente peIF4E que se sobreexpresaron en las células tumorales.…”
Section: -La Presentación De Nuevos Enfoques En El Tratamiento Delunclassified